Pengembangan Trainer Pembelajaran Smart Switch pada Mata Pelajaran Instalasi Penerangan Listrik di SMK N 1 Magelang: Penelitian - Zamtinah, Zamtinah; Aziz, Muchtar Abdul; Wardhana, Alex Sandria Jaya; Damarwan, Eko Swi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to produce a smart switch trainer learning media that is suitable for use in the Electrical Lighting Installation subject. The study uses the Research and Development (RnD) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 2 media experts, 2 material experts, and 47 grade XI students of SMK N 1 Magelang. Data collection was carried out through observation, interviews, and Likert scale questionnaires, with quantitative descriptive data analysis. The results of the development are in the form of a hardcase suitcase trainer equipped with a guidebook. The feasibility test showed that the smart switch trainer was declared suitable for use, with the validation results of material experts at 85% (very suitable), media experts 79% (suitable), and user responses 87% (very satisfactory).